2014
DOI: 10.1093/toxsci/kfu156
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Methotrexate-Induced Toxicity in Nonalcoholic Steatohepatitis

Abstract: Hepatic drug metabolizing enzymes and transporters play a crucial role in determining the fate of drugs, and alterations in liver function can place individuals at greater risk for adverse drug reactions (ADRs). We have shown that nonalcoholic steatohepatitis (NASH) leads to changes in the expression and localization of enzymes and transporters responsible for the disposition of numerous drugs. The purpose of this study was to determine the effect of NASH on methotrexate (MTX) disposition and the resulting tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 32 publications
(56 reference statements)
5
48
0
2
Order By: Relevance
“…In addition, MRP2/Mrp2 has garnered much interest due to the observation that in NASH, this transporter appears to be mislocalized , a phenomenon that also occurs in cholestasis and acute oxidative stress (Mottino et al, 2002;Sekine et al, 2006), and was confirmed in this study via immunohistochemistry. Several previous disposition studies have demonstrated a shift from biliary excretion of known MRP2/Mrp2 substrates and metabolites (Lickteig et al, 2007;Hardwick et al, 2012Hardwick et al, , 2014 to an increased systemic exposure, providing credence to the notion that MRP2/Mrp2 has diminished function in NASH. Accordingly, this study reports the altered disposition of another glucuronide, a common shared substrate for the MRP2/MRP3 system.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, MRP2/Mrp2 has garnered much interest due to the observation that in NASH, this transporter appears to be mislocalized , a phenomenon that also occurs in cholestasis and acute oxidative stress (Mottino et al, 2002;Sekine et al, 2006), and was confirmed in this study via immunohistochemistry. Several previous disposition studies have demonstrated a shift from biliary excretion of known MRP2/Mrp2 substrates and metabolites (Lickteig et al, 2007;Hardwick et al, 2012Hardwick et al, , 2014 to an increased systemic exposure, providing credence to the notion that MRP2/Mrp2 has diminished function in NASH. Accordingly, this study reports the altered disposition of another glucuronide, a common shared substrate for the MRP2/MRP3 system.…”
Section: Discussionmentioning
confidence: 62%
“…Although these have not been documented to complicate HDMTX, avoiding alcohol and controlling hepatitis infection before HDMTX is warranted to minimize risk. Conversely, existing steatohepatitis may increase methotrexate toxicity [25]. …”
Section: Management Of Specific Toxicities Associated With High-dose mentioning
confidence: 99%
“…Therefore, it is imperative that accurate diagnoses of disease be made so that correct liver phenotype can be either assessed empirically or attributed to the patient so that the correct drug dose is prescribed. In recent years, NASH is one liver disease for which there has been a considerable accrual of evidence to support its inclusion as an environmental factor in precision medicine (Clarke, et al, 2014a, 2014b; Fisher et al, 2009, 2008; Hardwick et al, 2011, 2012, 2014; N. Li et al, 2004; Lickteig et al, 2007).…”
Section: Sources Of Individual Variability In Precision Medicinementioning
confidence: 99%